Productivity enhancement in L-lysine fermentation using oxygen-enhanced bioreactor and oxygen vector - Wang, Jinduo; Wang, Shuo; Zhao, Siyu; Sun, Pengjie; Zhang, Zhen; Xu, Qingyang (Frontiers in Bioengineering and Biotechnology, 2023)
In this study, we designed and developed an oxygen-enhanced bioreactor to address that conventional bioreactors have meeting the oxygen supply conditions for L-lysine fermentation process. Methods. This bioreactor optimises the aeration mix using an internal liquid flow guide and multiple propellers. Results. Compared with a conventional bioreactor, it improved the kLa from 367.57/h to 875.64/h. The results show that the oxygen supply capacity of the oxygen-enhanced bioreactor is better than that of the conventional bioreactor. Its oxygenating effect increased the dissolved oxygen in the middle and late stages of fermentation by an average of 20%. The increased viability of Corynebacterium glutamicum LS260 in the mid to late stages of growth resulted in a yield of 185.3 g/L of L-lysine, 74.57% conversion between glucose and lysine, and a production intensity of 2.57 g/L/h, an increase of 11.0%, 6.01%, and 8.2%, respectively, over a conventional bioreactor. Oxygen vectors can further improve the production performance by increasing the oxygen uptake capacity of microorganisms. We compared the effects of different oxygen vectors on the production of L-lysine from LS260 fermentation and concluded that n-dodecane was the most suitable. Bacterial growth was smoother under these conditions, a 6.53% increase in lysine production, and a 5.83% increase in conversion. The different addition times of the oxygen vectors also affected the final yield and conversion, with the addition of oxygen vectors at 0 h, 8 h, 16 h, and 24 h of fermentation increasing the yield by 6.31%, 12.44%, 9.93%, and 7.39%, respectively, compared to fermentation without the addition of oxygen vectors. The conversion rates increased by 5.83%, 8.73%, 7.13%, and 6.13%, respectively. The best results were achieved by adding oxygen vehicles at the 8th hour of fermentation, with a lysine yield of 208.36 g/L and a conversion rate of 83.3%. In addition, n-dodecane significantly reduced the amount of foam produced during fermentation, which is beneficial for fermentation control and equipment. Conclusion. The new oxygen-enhanced bioreactor improves oxygen transfer efficiency, and oxygen vectors enhance the ability of cells to take up oxygen, which effectively solves the problem of insufficient oxygen supply during lysine fermentation.